PENGARUH FINANCIAL KNOWLEDGE DAN INCOME MELALUI LOCUS OF CONTROL TERHADAP FINANCIAL MANAGEMENT BEHAVIOR - Sri Ayuni, Ni Made; Sinta Lestari, Ni Komang Desi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022DO - 10.24843/EEB.2022.v11.i09.p11, 2022)
The purpose of this study was to determine the effect of Financial Knowledge and Income through Locus Of Control on Financial Management Behavior of STIE Satya Dharma students. The research method used is a quantitative method, with  data collection techniques used in the form of questionnaires distributed using google form media with a Likert scale as a measuring tool, the selected respondents are students of STIE Satya Dharma Semester 8 who have worked with a total of 85 respondents. This study uses the SEM-PLS structural equation analysis method by utilizing the SmartPLS application. From the results of the analysis it was found that there is a positive and significant influence between financial knowledge, income and  locus of  control on the financial management behavior of STIE Satya Dharma students, there is a positive and significant influence between financial knowledge and income on the locus of control of STIE Satya Dharma students, and there is a positive and significant influence between financial knowledge and income through locus of control on the financial management behavior of STIE Satya Dharma students.